Civil Law Reform Toward Substantive Justice: A Comparative Study Between Indonesia and Spain - Ohoiwutun, Martinus Guntur; Rahman, Ali; Pozo, Antonio Gutierrez (Batulis Civil Law Review, 2026)
Introduction: Civil law reform increasingly grapples with a persistent dilemma: how to preserve doctrinal coherence while ensuring outcomes that realise substantive justice in concrete disputes. This article analyzes this tension by comparing contemporary legal trajectories in Indonesia and Spain, focusing on whether existing civil codes, procedural frameworks, and judicial reasoning can effectively align legal certainty with equitable results.Purposes of the Research: The purpose of this study is to examine the interaction between formal rigidity and material fairness within civil law systems. Specifically, it aims to compare the three analytical axes of good faith principles, equitable evidentiary and remedial design, and institutional mechanisms (like appellate oversight) in Indonesia and Spain to guide judicial discretion without eroding predictability.Methods of the Research: This research employs a normative–comparative approach. It focuses on studying the law 'in the books' and 'in action' by analyzing civil codes, procedural frameworks, judicial precedents (Supreme Court circulars in Indonesia, Constitutional and Supreme Court interpretations in Spain), and scholarly debates, particularly in consumer and contractual disputes.Results / Main Findings / Novelty/Originality of the Research: The findings reveal both jurisdictions confront parallel challenges: formal rigidity, unequal procedural access, and gaps between normative ideals and lived justice. This study proposes a progressive framework that combines procedural refinement, principled judicial discretion, and responsive legislative adjustment, illustrating how civil law systems can evolve towards judgments that are both predictable and experienced as substantively just.